LANGUAGE VARIATION OF BURU YOUTH ON SOCIAL MEDIA: A SOCIOLINGUISTIC STUDY - Anita Dwi Lestari; Taufik Taufik; Susiati Susiati; Azwan Azwan (Jurnal Kata, 2025)
This study aims to identify and analyze the language variations and language functions used by Buru teenagers in their interactions on social media, particularly TikTok and Facebook, through a sociolinguistic approach. The results of the study show that the language variation of Buru adolescents on TikTok and Facebook is influenced by social, situational, and technological factors, with four main forms: dialect (local identity), usage (communicative function), formality, and medium (a mix of spoken and written forms). The most dominant variation is formality, characterized using casual and intimate language that reflects expressive communication, the use of slang and local dialect, and the strengthening of closeness and solidarity among adolescents. Furthermore, six functions of language variation were identified, namely emotive, directive, phatic, referential, metalingual, and imaginative functions. Among these, the emotive function is the most dominant.